Association of Human Leukocyte Antigen (HLA) class II (DRB1 and DQB1) alleles and haplotypes with Rheumatoid Arthritis in Sudanese patients - Ali, Adil Ahmed; Khalid, Khalid Eltahir; Mohammed, Somaya Elhaj; Akhtar, Mohammed Salman; Saeed, Osman Khalafalla (Frontiers in Immunology, 2023)
The aim of this study was to determine the Human Leukocyte Antigen (HLA) class II (DRB1 and DQB1) alleles and haplotype frequency in Rheumatoid Arthritis (RA) in the Sudanese population. The frequency of HLA-DRB1 and -DQB1 alleles and DRB1-DQB1 haplotypes were determined in 122 RA patients and 100 controls. HLA alleles were genotyped by the polymerase chain reaction-sequence specific primers (PCR-SSP) method. In RA patients, HLA-DRB1*04 and *10 alleles were high in frequency (9.6% vs 14.2%, P = 0.038 and P = 0.042, respectively), and dependently on anti-citrullinated protein antibodies (ACPAs) seropositivity (P = 0.044 and P = 0.027, respectively). In contrast, the frequency of the HLA-DRB1*07 allele was significantly low in patients than in controls (11.7% vs 5.0%, P = 0.010). Moreover, the HLA-DQB1*03 allele was strongly associated with RA risk (42.2%, P = 2.2x10-8), whereas, HLA-DQB1*02 and *06 showed protective effects against RA (23.1% and 42.2%, P = 0.024 and P = 2.2x10-6, respectively). Five different HLA haplotypes, DRB1*03-DQB1*03 (P = 0.00003), DRB1*04-DQB1*03 (P = 0.00014), DRB1*08-DQB1*03 (P = 0.027), DRB1*13-DQB1*02 (P = 0.004), and DRB1*13-DQB1*03 (P = 3.79x10-8) were significantly associated with RA risk, while 3 protective haplotypes, DRB1*03-DQB1*02 (Pc = 0.008), DRB1*07-DQB1*02 (Pc = 0.004), and DRB1*13-DQB1*06 (Pc = 0.02) were identified. This is the first study determining the association between HLA class II alleles and haplotypes and RA risk in our population.